Supporting Indigenous Family Caregivers of Children with Life-Threatening and Life-Limiting Illness in One Canadian Province: Healthcare Providers’ Perspectives - Jill M. G. Bally; Meridith Burles; Amaya Widyaratne; Victoria A. Spurr; Heather Hodgson-Viden; Roona Sinha (Children)
Background: Indigenous peoples in Canada endure lasting effects of colonialism including racism, marginalization, and social, political, and geographic inequities resulting in disproportionate rates of disease and inequitable healthcare. Indigenous infants and children in Canada experience a high incidence of birth complications and illnesses, and families are often left to navigate the care of their child with limited resources. Accordingly, improved, culturally responsive and safe healthcare is needed to enhance child outcomes and optimize family well-being. Purpose and Methods: A qualitative study was conducted by our research team including family members of Indigenous children with serious illnesses, a Cultural Advisor, researchers, and pediatric clinicians. In one component of the study, we explored pediatric healthcare providers’ (HCPs) experiences of caring for Indigenous families of children with serious illness. A purposive sample of 19 pediatric healthcare providers took part in semi-structured qualitative interviews or one focus group. The data were analyzed thematically to identify common experiences and priorities for improved supportive healthcare. Findings: Five themes were identified representing insights from pediatric HCPs, with a focus on barriers to effective healthcare at the interpersonal, institutional, and system levels for seriously ill Indigenous children and their families. Ideas for enhancing the social and cultural responsiveness and safety of supportive healthcare were identified. Implications and Conclusions: The findings offer valuable insights and strategies for HCPs to support holistic, comprehensive, and culturally safe and responsive healthcare.